2020
DOI: 10.3390/ijms21145148
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Methionine Aminopeptidase 2 in Lymphangiogenesis

Abstract: During the metastasis process, tumor cells invade the blood circulatory system directly from venous capillaries or indirectly via lymphatic vessels. Understanding the relative contribution of each pathway and identifying the molecular targets that affect both processes is critical for reducing cancer spread. Methionine aminopeptidase 2 (MetAp2) is an intracellular enzyme known to modulate angiogenesis. In this study, we investigated the additional role of MetAp2 in lymphangiogenesis. A histological staining of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A number of studies have been reported that factors involved in angiogenesis also have an effect on lymphangiogenesis. For instance, MetAp2 has been reported to have a dual role in the formation of blood and lymphatic vessels [ 5 ]. EGR1 has been demonstrated to have a critical role in blood vessel formation [ 16 – 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have been reported that factors involved in angiogenesis also have an effect on lymphangiogenesis. For instance, MetAp2 has been reported to have a dual role in the formation of blood and lymphatic vessels [ 5 ]. EGR1 has been demonstrated to have a critical role in blood vessel formation [ 16 – 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The progression of lymphangiogenesis involves a number of molecules and pathways. VEGF is suggested to be the most important regulator in lymphatic generation and is wildly used as a therapeutic target against diseases associated with lymphatic generation, such as cancer [ 5 , 6 ]. However, there are many other factors involved in lymphangiogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the studies performed focused on the impact of MetAP2 inhibition on the tumor and endothelial cell compartments but did not investigate modulation of the immune system. Immune modulatory effects of MetAP2 inhibition have been investigated anecdotally, but further, more systematic studies in immune-competent mouse tumor models are required to better characterize its function ( 32, 33 ). Further development of M8891 will be managed by the Oncoteq AG subsidiary of Cureteq AG ( 34 ), which licensed M8891 from Merck KGaA following the determination of the recommended phase II dose in a phase Ia trial ( 35 ) and the strategic portfolio decision by Merck KGaA.…”
Section: Discussionmentioning
confidence: 99%
“…The role of methionine aminopeptidase 2 (MetAp2), an intracellular enzyme known to modulate angiogenesis, in lymphangiogenesis has been described by Rawnaque Esa et al [9]. The genetic and biochemical manipulation of MetAp2 confirmed the dual activity of the enzyme in both vascular and lymphatic remodulation in cell function assays and in a zebrafish model.…”
mentioning
confidence: 88%